Dampak Lidah Yang Tidak Terkendali Dalam Hubungan Sosial Perspektif: Yakobus Dan Relevansinya Dalam Masyarakat Kontemporer - Rini Ndraha; Abad Jaya Zega (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The tongue is sharper than a sword, meaning that whatever comes out of a person's mouth will definitely have the effect of killing someone physically, mentally and spiritually. Therefore, as a human being, you must be careful not to harm yourself or others. Even though The tongue physically feels soft because it has no bones, but if the tongue's ability to speak is not used wisely, the tongue becomes sharper than a sword. The tongue is able to cut and tear hearts without harming anyone's body. The tongue is sharper than a sword, which means we have to be careful in every word we say so as not to harm ourselves. The sin of the tongue is a sin that comes out of the mouth and is expressed in words that offend other people's feelings. Language is only a small part, but language can also detect a person's physical condition through speech like the one above. This means that someone can find out whether another person is an adult or not, all of this can be known through their words. With his tongue, man praises God's name, but with the same tongue, he curses creatures created in the image and likeness of God. It is in the same language that blessings and curses come (James 3: 1-12), where James emphasizes: